Pengaruh Gerakan PBLHS, Proyek Penguatan Profil Pelajar Pancasila, Dan Budaya Positif Terhadap Karakter Peduli Lingkungan - Mucholifah, Umi Hanik; Kadeni, Kadeni; Purwananti, Yepi Sedya (Universitas Nusantara PGRI Kediri, 2024)
Human character and behaviour play an important role in determining the quality of the environment, character education is the key to instilling environmental care character in the younger generation. This study aims to determine the effect of the PBLHS Movement, the Pancasila Student Profile Strengthening Project, and positive culture on the environmental care character of Samir State Elementary School students in the 2023/2024 academic year. By using a correlational quantitative approach. Population 98 students using saturated sample technique, data collected through questionnaires, and analysed using t test and f test. The results showed that PBLHS Movement, P5, and positive culture partially and simultaneously had a significant effect on students' environmental care character, with an Fcount value of 390.458 > Ftable 2.70 and a significance level of 0.000 < α = 0.05. This finding confirms the importance of the integration of the three variables in shaping holistic and sustainable environmental care character. It is recommended that schools collaborate with policy makers and student guardians so that students' environmental care character is stronger and more cultured.